A Research-Based Summary on Trace Minerals for Cattle: VM245/VM245, 10/2021 - Bittar, João H. Jabur; Palomares, Roberto A. (EDIS, 2021)
Producers can utilize mineral supplementation to improve cattle production and herd health, which has the potential to reduce antibiotic usage. This publication presents a summary on trace minerals for cattle. Written by João H. Jabur Bittar and Roberto A. Palomares, and published by the UF/IFAS Veterinary Medicine—Large Animal Clinical Sciences Department, October 2021.